2004
DOI: 10.1016/s0002-9440(10)63111-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of a Myc Target Gene Mina53 in Human Colon Cancer

Abstract: Mina53 is a novel Myc target gene that we previously demonstrated to be involved in cell proliferation. We studied, here, the expression of Mina53 in colon cancer to examine its possible role in carcinogenesis. We generated a specific monoclonal anti-human Mina53 antibody and found that colon tumor cell lines expressed Mina53 highly. We also found that expression

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 39 publications
6
91
0
1
Order By: Relevance
“…Expression of mina53 is increased during cell proliferation, and specific inhibition of mina53 expression by an RNA interference method suppressed cell proliferation in some cultured cell lines (25,26). Recently, we generated a specific monoclonal antibody against human Mina53 protein and found that expression of Mina53 is frequently increased in human colon cancer (26). Here we show that Mina53 is highly expressed in most ESCC cells and that its expression level in tumors relates to the outcome of patients with ESCC.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Expression of mina53 is increased during cell proliferation, and specific inhibition of mina53 expression by an RNA interference method suppressed cell proliferation in some cultured cell lines (25,26). Recently, we generated a specific monoclonal antibody against human Mina53 protein and found that expression of Mina53 is frequently increased in human colon cancer (26). Here we show that Mina53 is highly expressed in most ESCC cells and that its expression level in tumors relates to the outcome of patients with ESCC.…”
Section: Introductionmentioning
confidence: 65%
“…One hybridoma secreting an IgG2a antibody, clone M532, was used in this study. The specificity of M532 to human Mina53 was demonstrated in our previous study (26). The antibody was produced as ascitic fluid in prestane-preinjected mice and purified.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations